x + y + z = 3
x - y - z = -1
2x + y + 5z = 8
adding the first two equations term for term will yield an equation easy to solve for x
adding the second and third equations will yield an equation in terms of x and z
use the value of x determined in the first step above to determine z, then use any of the equations to determine y
one more time
x - y - z = -1adding the second and third equations will yield an equation in terms of x and z
2x + y + 5z = 8
--------------------
3x + 4z = 7
substitute 1 in for x, determine z, then determine y using any of the original equations